Urbanization growth dynamic model of metropolitan city Karachi - Mansoor, Asif; Khan, Nasiruddin; Hussain, Mushtaq; Muhammad , Ayaz (2008)

(untitled)
The city Karachi has grown from a small fishing village to the enormous metropolis and now becomes the biggest and most industrialized city of Pakistan due to its multi-ethnic character. It population now exceeds 12 million (approximately) and its current growing rate is about 5% per year. This phenomenal, growth of the metropolitan city affects nomads as well as high class society and covers almost all aspect of life such as social, economical, political, sociological, psychological etc. This unchecked increase becomes the origin of the problems of slums, katchi abaadis, and encroachment. It has been estimated that one-third of the total population resides in squatter settlements and slums which results in chronic shortage of dwelling units, water supply, public transport, and civic amenities such as schools, hospitals , parks and playgrounds. This rapid growth of population is a burning issue for developing and governmental agencies. In this study attempts has been made to provide a systematic analysis of the population growth in the metropolitan city Karachi and model have been constructed by using the available demographic data. Finding of this model will serve as a basis for making planning to control rate of population growth in both Urban and Rural areas and develop a strategy to attain higher level of structural change of urbanization.